Elemental Mapping of Lithium Diffusion in Doped Plant Leaves Using Laser-Induced Breakdown Spectroscopy (LIBS). Issue 4 (April 2019) - Singh, Vivek K.; Tripathi, Durgesh Kumar; Mao, Xianglei; Russo, Richard E.; Zorba, Vassilia
Mapping of element distributions and diffusion processes in plant tissue has great significance for understanding the systematic uptake, transport, and accumulation of nutrients and harmful elements in plants, and for studying the interaction between plants and the environment. In this work, we used laser-induced breakdown spectroscopy (LIBS) to study the elemental accumulation of Li and its diffusion in plant leaves. The spatially resolved information that LIBS offers, combined with its high sensitivity to light elements make this technology highly advantageous for the analysis of Li. Laser-induced breakdown spectroscopy mapping of Li-doped leaf samples is used to directly visualize the diffusion of Li in the plant leaf and study its distribution as a function of LiCl solution exposure time. Our findings demonstrate that diffusion of Li in plant leaves occurs though their veins (i.e., bundles of vascular tissue) and that Li concentration decreases as we move away from the LiCl exposure site. These results underline the importance of veins in transportation of toxic elements in plants, and mapping of their distribution can be instrumental in the development of possible remediation approaches for managing Li toxicity.